2021
DOI: 10.1007/s00426-021-01522-5
|View full text |Cite
|
Sign up to set email alerts
|

Meditation affects word recognition of meditation novices

Abstract: This work represents one of the first attempts to examine the effects of meditation on the processing of written single words. In the present longitudinal study, participants conducted a lexical decision task and rated the affective valence of nouns before and after a 7-week class in mindfulness meditation, loving-kindness meditation, or a control intervention. Both meditation groups rated the emotional valence of nouns more neutral after the interventions, suggesting a general down-regulation of emotions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…However, in the present study, none of the changes in experiencing emotions was positively associated with improved reading comprehension. This may be related to the fact that, unlike in the word recognition studies of Lusnig et al, (2020Lusnig et al, ( , 2022, the text materials used in the present work had no affective connotation and did not call for a substantial affective evaluation.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, in the present study, none of the changes in experiencing emotions was positively associated with improved reading comprehension. This may be related to the fact that, unlike in the word recognition studies of Lusnig et al, (2020Lusnig et al, ( , 2022, the text materials used in the present work had no affective connotation and did not call for a substantial affective evaluation.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we assumed that emotion regulation could be another underlying mechanism of meditation that might lead to enhanced text processing. Lusnig et al, (2020Lusnig et al, ( , 2022 showed that meditation can affect single word processing and also neutralize valence ratings on emotional words. However, in the present study, none of the changes in experiencing emotions was positively associated with improved reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations